MATEMÁTICA FINANCEIRA E PLANILHAS ELETRÔNICAS: UMA ABORDAGEM COM A INCORPORAÇÃO DE RECURSOS COMPUTACIONAIS - Duda, Rodrigo (2014)
This paper has as its goal to propose a new alternative approach to the progressions and financial math teaching, with the incorporation of technological resources. Financial math is a theme of great relevance, since it is a field of direct application of various mathematical concepts studied throughout school education. One of the concepts that used is the study of geometric and arithmetic progressions. In order to study those, an approach based on recurrence relations is proposed. Due to the relevance of financial math in the student’s school formation, it is analyzed the ways the frequencies in which the theme is addressed in the High School National Exam and in the selection processes of the Ponta Grossa State University. With the goal of stimulating the algebraic manipulation and understanding of the financial math formulas variables, it is proposed the incorporation of the technological resources, in particular, of electronic spreadsheets, in classes about the theme. Through the tool, it is proposed the viability of financial math simulators in the classroom, seeking the diversification of activities. It is also contemplated the development of an app that operates under the Android Platform, seeking portability and sharing of the simulators that can be built in the classroom.